Positive Psychological Impacts of Cooking During the COVID-19 Lockdown Period: A Qualitative Study - Güler, Ozan; Haseki, Murat İsmet (Frontiers in Psychology, 2021)
This study aims to explore the positive psychological effects of culinary experiences during the COVID-19 lockdown days. Qualitative research methods adopted to provide a deeper understanding. Data was collected through a structured online survey from 30 participants in Turkey. This occurred between April 10th and June 3rd, 2020 when the strict confinement measures were applied. Content analysis was deductively applied according to the Stebbins’s Theory of Casual vs. Serious Leisure which classifies the well-being according to characteristics of leisure experiences. The results revealed that at the first stage people went into the kitchen with the motivation of pure happiness and relaxation indicating hedonic well-being. However, people who intended to spend time with culinary activities with the expectations of pure happiness left the kitchen with eudaimonic outcomes by gaining special skills and knowledge, self-actualization and self-enrichment. When these outcomes are evaluated based on the Stebbins’s theoretical framework, culinary activities have both casual and serious leisure experience characteristics in terms of psychological well-being. It is understood that culinary activities have versatile leisure characteristics. Thanks to the culinary activities, people do not only obtain pure happiness and relaxation but can draw wider inferences about their life by realizing their own potential during the psychologically challenging COVID-19 lockdown days.